Bolivian sub-national revenues: A review - Beatriz Muriel H. (Institute for Advanced Development Studies (INESAD), 2011)
This papers reviews main topics concerning sub-national revenues (intergovernmental transfers and taxes) and discusses some policy options to develop own sub-national revenues. The review covers the political-legal framework and the fiscal outcomes, finding that: i) intergovernmental transfers policies have expanded over time, generating inequity problems, principally at the departmental level; ii) sub-national revenues depend mostly on intergovernmental transfers; this has generated high levels of vertical imbalances, mainly for department governments whose revenues rely mostly on the hydrocarbons sector; and iii) lack of adequate tax policies that promote fiscal effort and equity led to large horizontal imbalances in municipal per capita tax collection, unrelated to poverty or human development differences. In this regard, policy options were discussed to increase own sub-national revenues, taking into account political and social discussions, the economic, fiscal and legal base, and relevant tax principles. The main recommendations are: i) to promote in-kind contributions (materials and labour) at the municipal level, especially in poor rural municipalities; ii) to improve municipal tax administration supporting the continuation of the RUAT's work and improving the registry with the new census; and iii) to evaluate the possibility of redefining the RC-IVA as a personal income tax shared between the central government and the departments.
Keywords: H20; H71; H73; H77; K00; 330; Bolivia; fiscal decentralization; revenues; taxes; intergovernmental transfers; Dezentralisierung; Finanzausgleich; Bolivien